On Elena Văcărescu’s visit to Portugal (1864-1947) - Navas Sánchez-Élez, Mª Victoria (Revista de Filología Románica, 2012)
This papers aims to briefly present the visit that the Romanian author Elena Văcărescu paid to Portugal during the first part of the 20th century; she was a good friend to the Portuguese writers Virgínia Vitorino and Fernanda de Castro. Văcărescu had also an interest in Portuguese literature.
Keywords: Elena Văcărescu; Virgínia Vitorino; Fernanda de Castro; Portuguese literature